Novel SF5-Anilines and SF5-Aryl Ethers from SF5-Substituted Potassium Aryl Trifluoroborates - Joliton, Adrien; Carreira, Erick M. (Synlett, 2015)
The copper-catalyzed coupling of SF5-substituted potassium aryl trifluoroborates with amines and alcohols is reported. This method provides a simple access to novel 3-pentafluorosulfanyl-substituted anilines and aryl ethers, which are potential important building blocks for drug discovery and agrochemicals.
Keywords: pentafluorosulfanyl; copper; arenes; ethers; anilines